1971
DOI: 10.1192/bjp.118.544.319
|View full text |Cite
|
Sign up to set email alerts
|

Parental Deprivation, Family Background and Female Delinquency

Abstract: The purpose of this article is twofold. Firstly as a contribution to the literature of female delinquency, a subject that has attracted little contemporary attention, with one notable exception, the essentially psychiatric study of a year's intake into a classifying Approved School by Cowie, Cowie and Slater (1968). Secondly as an examination of the hypothesis that early adverse experiences are related to female delinquency in particular and to behaviour disturbance in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…These authors compared 500 delinquent boys to a control group, matched on criteria of age, gender, IQ, ethnic and social background, and observed a higher proportion of middle-born children in their sample of delinquents (see, for similar results, Lee and Newson, 1954;Hirschi, 1969;West and Farrington, 1973;Leflore, 1988). These observations may be contrasted to discordant findings which either do not verify any effect of ordinal position (Ferguson, 1952;Johanson, 1968;Barry and Barry, 1969), or report inconsistent effects whereby later-borns would be more (Berg et al, 1967) or less (Biles, 1971;Koller, 1971) engaged in deviance. Such inconsistencies suggest that the effects of ordinal position on delinquency are modulated by factors that were not systematically controlled in previous research.…”
Section: Evidence Of the Birth-order Effect On Delinquencymentioning
confidence: 57%
“…These authors compared 500 delinquent boys to a control group, matched on criteria of age, gender, IQ, ethnic and social background, and observed a higher proportion of middle-born children in their sample of delinquents (see, for similar results, Lee and Newson, 1954;Hirschi, 1969;West and Farrington, 1973;Leflore, 1988). These observations may be contrasted to discordant findings which either do not verify any effect of ordinal position (Ferguson, 1952;Johanson, 1968;Barry and Barry, 1969), or report inconsistent effects whereby later-borns would be more (Berg et al, 1967) or less (Biles, 1971;Koller, 1971) engaged in deviance. Such inconsistencies suggest that the effects of ordinal position on delinquency are modulated by factors that were not systematically controlled in previous research.…”
Section: Evidence Of the Birth-order Effect On Delinquencymentioning
confidence: 57%
“…It has been shown that disruptive parental homes are as equally distributed as inadequate ones, and that these factors are not associated with a recidivist course or with any other factor. In Australia, Koller (1971) made an investigation of the significance of separation experience in delinquency among girls at a training school. Parental loss and deprivation was five times more prevalent for delinquents, compared with controls; a half experienced this loss before reaching school age and one-third experienced a second loss during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…at MOUNT ALLISON UNIV on June 25, 2015 isp.sagepub.com Downloaded from However, when Koller (1971) studied this problem among 121 girls at a training sehool, he found maternal loss no more prevalent than paternal loss. This suggest that subsequent separation experiences interact with previous ones in precipitating delinquency and depression.…”
mentioning
confidence: 91%
“…For example, Koller (1971); Koller and Castanos (1969). 24 Willson (1979) supplies some background data on women prisoners in New South Wales.…”
Section: Resultsmentioning
confidence: 99%